Bis[1,3-bis-(diphenyl-phosphino)propane-κP:P']silver(I) bis-(chloro-difluoro-acetato-κO)triphenyl-stannate(IV). - Teo, Y.Y.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2008)
In the title salt, [Ag(C(27)H(26)P(2))(2)][Sn(C(6)H(5))(3)(C(2)ClF(2)O(2))], the Ag(I) atom exists in a tetra-hedral coordination geometry formed by four P atoms [Ag-P = 2.460 (1)-2.501 (1) Å], whereas the Sn(IV) atom exists in a trans-trigonal-bipyramidal coordination geometry formed by two O [Sn-O = 2.208 (3) and 2.233 (3) Å] and three C atoms [Sn-C = 2.115 (4)-2.128 (4) Å;(Σ C-Sn-C)= 360.0 (6)°].